2017
DOI: 10.1111/liv.13492
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and histopathological analysis of cholangiolocellular differentiation trait in intrahepatic cholangiocarcinoma

Abstract: Background & Aims: Intrahepatic cholangiocarcinoma (iCCA) is a heterogeneous entity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 21 publications
1
56
0
Order By: Relevance
“…The presence of a stemness molecular signature is usually viewed, and confirmed in a recent small series as an adverse prognostic factor in hepatic malignancies . Whereas the worse prognosis for HCC with K19 positivity has been well demonstrated, there is good prognostic evidence from two recent Asian clinicopathological studies for CLC: One compared CLC to iCCA and another compared ciCCA‐CLC to iCCA without CLC . Nevertheless, a worse postoperative survival rate has been reported in the group of cHCC‐CCA exhibiting >5% stem cells .…”
Section: Molecular Pathology Of Chcc‐ccamentioning
confidence: 94%
“…The presence of a stemness molecular signature is usually viewed, and confirmed in a recent small series as an adverse prognostic factor in hepatic malignancies . Whereas the worse prognosis for HCC with K19 positivity has been well demonstrated, there is good prognostic evidence from two recent Asian clinicopathological studies for CLC: One compared CLC to iCCA and another compared ciCCA‐CLC to iCCA without CLC . Nevertheless, a worse postoperative survival rate has been reported in the group of cHCC‐CCA exhibiting >5% stem cells .…”
Section: Molecular Pathology Of Chcc‐ccamentioning
confidence: 94%
“…In this study, the proliferation class was demonstrated to exhibit a more aggressive clinical behavior, whereas the inflammation subclass defined a class of iCCA with a more favorable prognosis. In a separate study, iCCA with cholangiocellular differentiation was found to resemble an inflammation‐related state, while iCCA without cholangiocellular differentiation resembled a proliferation subtype . A subset of human CCAs exhibiting a strong up‐regulation of ERBB2 signaling in the epithelial cell compartment of the tumor together with a concomitant overexpression in the tumor stroma of inflammatory cytokines, including interleukin‐6, was reported to be predictive of a highly malignant phenotype .…”
Section: Molecular Profiling and Icca Heterogeneitymentioning
confidence: 94%
“…In a separate study, iCCA with cholangiocellular differentiation was found to resemble an inflammationrelated state, while iCCA without cholangiocellular differentiation resembled a proliferation subtype. (31) A subset of human CCAs exhibiting a strong up-regulation of ERBB2 signaling in the epithelial cell compartment of the tumor together with a concomitant overexpression in the tumor stroma of inflammatory cytokines, including interleukin-6, was reported to be predictive of a highly malignant phenotype. (32) Other relevant genomic alterations that include fibroblast growth factor receptor 2 (FGFR2) fusions and isocitrate dehydrogenase 1/2 (IDH1/2) mutations may have prognostic significance for patients with iCCA and are emerging as targeted therapy options (see following section).…”
Section: Molecular Profiling and Icca Heterogeneitymentioning
confidence: 99%
“…iCCA with cholangiolocellular differentiation resembling an inflammation‐related subtype revealed less aggressive histopathological features compared to iCCA without cholangiolocellular differentiation resembling a proliferation subtype. Accordingly, the former showed more favourable clinical outcomes, including overall survival, than iCCA without cholangiolocellular differentiation …”
mentioning
confidence: 95%
“…Accordingly, the frequency of perineural invasion, lymph node metastasis, vascular invasion, intrahepatic metastasis and extrahepatic recurrence of large bile duct type (mucinous) iCCAs were significantly higher than that of small bile duct type (mixed) iCCAs, and, indeed, the survival of patients with the large bile duct type iCCAs was the worst . Very recently, the histopathological distinction of cholangiolocellular differentiation of iCCA has been correlated with its genome‐wide molecular features and clinical significance . Based on cholangiolocellular differentiation status, iCCAs were stratified into iCCA with or without cholangiolocellular differentiation.…”
mentioning
confidence: 99%